2022
DOI: 10.4103/ijnmr.ijnmr_213_20
|View full text |Cite
|
Sign up to set email alerts
|

Health Anxiety among Nurses Caring for Patients with Covid-19

Abstract: Background: Medical personnel, especially nurses, are at the forefront of the global COVID-19 epidemic. This study was conducted with the aim to evaluate the level of health anxiety in nurses caring for patients with COVID-19. Materials and Methods: This cross-sectional, descriptive study was performed on the 340 nurses working in 3 selected educational and medical centers affiliated with Zanjan University of Medical Sciences, Iran. The participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Since our study was conducted on frontline nurses who directly cared for COVID patients, it is reasonable that the level of health anxiety in these nurses is high. Consistent with this finding, in other studies, the level of health anxiety of the medical staff, especially the frontline nurses, was high [ 9 , 17 , 18 , 50 ]. Frontline nurses face much more psychological stress due to their work environment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since our study was conducted on frontline nurses who directly cared for COVID patients, it is reasonable that the level of health anxiety in these nurses is high. Consistent with this finding, in other studies, the level of health anxiety of the medical staff, especially the frontline nurses, was high [ 9 , 17 , 18 , 50 ]. Frontline nurses face much more psychological stress due to their work environment.…”
Section: Discussionsupporting
confidence: 86%
“…Front-line nursing staff suffer from psychological distress due to close interaction with patients [ 5 , 6 ]. One of the psychological issues that have plagued frontline nurses during the COVID-19 outbreak is health anxiety [ 7 9 ]. In one study, the prevalence of health anxiety in nurses caring for COVID-19 patients was reported more than 90% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation